Patterns of online seeking and providing help among adolescents: a preliminary study. Issue 1 (2nd January 2022) - Lipshits-Braziler, Yuliya; Amram-Vaknin, Sima; Pesin-Michael, Gali; Tatar, Moshe
ABSTRACT: We proposed a typology of adolescents' online support-related behaviours based on two facets: help-seeking and help-providing: (1) Transceivers seek and provide help; (2) Receivers seek help but do not provide it; (3) Transmitters provide help, yet do not seek it; and (4) Idlers refrain from seeking and providing help. Of the 528 adolescents, the largest group are Transceivers (45%), and they seek help mainly from peers through social networking sites, around social issues. For Receivers (5%) the most important facilitator of seeking help is anonymity. Transmitters (16%) refrain from seeking help due to self-reliance. Idlers (34%) refrain from seeking help due to their preference to face-to-face encounters. The characteristics of the four patterns are discussed in light of counselling implications.